Comparison of Agricultural Machine Tool Needs in Food Crop Farming on Direct Surveys and Integrated Planting Calendar Information Systems - Isran Mohamad Pakaya; Hermantoro Hermantoro; Eka Suhartanto (Akademi Komunitas Perkebunan Yogyakarta, 2023)
This study aims to compare the needs of agricultural machinery in rice farming through direct surveys and integrated Planting calendar information systems. This research was conducted in July-September 2020 in Boalemo Regency. The number of respondents in the study was 54 farmers. Based on the study's results, it is known that agricultural machinery is very necessary. This is stated by 91% of respondents stating they always use agricultural machinery in their farming business. Agricultural machinery, hand tractors, power theresors, and combine harvesters are included in the high category that farmers often use with percentages of 9, 8.15%, 85.19%, and 72.22%. Rice transplanters are still in the low category 40.74%, due to small land ownership and lack of socialization. The use of agricultural machinery can save costs, reduce labour, and speed up work. Based on the calculation of the adequacy status of the hand tractor, rice transplanter, and power thereser is appropriate. However, in the combine harvester there is a difference in a calculation, manually, the status is less, and in the interactive application the status is saturated. This is due to differences in available tools, and delays in updating data on the planting calendar. So it is necessary to regularly input and repair existing data on the word. Analysis of the B/C ratio of hand tractor, rice transplanter and power thereser is 1. 0, will the business of agricultural machinery is profitable and feasible. While the combine harvester value B/C ratio 1. 0, the exploitation of agricultural machinery is detrimental and not feasible.